ANALISIS DAMPAK KERJASAMA BILATERAL TIONGKOK SEBAGAI SOLUSI PERMASALAHAN INFRASTRUKTUR PELABUHAN INDONESIA - Aditya Misbach Lesmana,; Hanifah Maulidiya Madani,; Rey Noor Al Rasyid,; Aurelia Putri Hertama,; Efi Safitri, (Jurnal Cakrawala Ilmiah, 2023)
Indonesia as a maritime country with abundant natural resources is considered to have not been able to optimize its potential, especially in the field of port infrastructure. The efforts made by the Indonesian government to realize infrastructure projects are by cooperating with China. In this case, Indonesia is taking advantage of investment opportunities from the One Belt One Road (OBOR) or silk route policy. Writing in this journal uses the literature review method, which aims to produce an analysis and synthesis of existing knowledge from researchers regarding the topic to be raised. After writing the journal, the analyst believes that the OBOR project has a goal of expanding China's connectivity globally. As a maritime country, Indonesia is a country with great potential to obtain investment funds for the development of marine infrastructure. But on the other hand, Indonesia is also facing challenges that will have an impact on the economic sector, and can threaten the security and defense sector in Indonesia's maritime area